2022
DOI: 10.1007/s00170-022-08947-1
|View full text |Cite
|
Sign up to set email alerts
|

A drilling case study in polymer composites reinforced by virgin and recycled carbon fibres (CFRP and rCFRP) to analyse thrust force and torque

Abstract: A great deal of attention is currently paid to recycling or reusing carbon fibres, as it improves sustainability and the lifetime of carbon products. The applicability of recycled carbon fibre–reinforced polymer (rCFRP) composite materials is supported by the results of material scientists; however, the machinability of rCFRPs has not been analysed yet. The machinability of virgin and rCFRPs was compared by analysing cutting force and torque in drilling. Six different CFRPs (virgin and recycled CFRPs with diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The absolute percentage error (APE) was used to characterise the adequacy of the F t predictions, as expressed by Eq. (6).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The absolute percentage error (APE) was used to characterise the adequacy of the F t predictions, as expressed by Eq. (6).…”
Section: Methodsmentioning
confidence: 99%
“…However, their manufacturing is costly, and the life cycle of products made from carbon and glass fibres is relatively short. Their recycling and/or reusing is difficult or often not solvable [6][7][8]. Therefore, researchers developed novel fibrous composites using organic and inorganic reinforcing fibres.…”
Section: Introductionmentioning
confidence: 99%
“…Fig. 1 The experimental machining setup: a working environment and b the applied coated solid carbide twist drill The factor spaces and levels were determined based on suggestions of cutting tool producers and on previous studies [27,28]. The drilling experiments were conducted in a dry condition, randomised order.…”
Section: Materials Tools and Machinesmentioning
confidence: 99%
“…Xu et al [ 40 ] performed the conventional drilling of CFRP and resulted in an inverse relation of feed rate and cutting speed with the composite drilling temperature to alleviate the matrix glass transition. Geier et al [ 41 ] performed a comparative study of virgin and recycled CFRP drilling concerning torque and thrust force. It was concluded that higher torque and cutting force are produced in recycled CFRP specimens compared to the virgin.…”
Section: Introductionmentioning
confidence: 99%